Enzymatic hydrolysis as a valorization strategy of bovine lungs: Optimization of process variables and study of antioxidant capacity - Martinez, Fernanda Gabriela; Ambrosi, Vanina; Rocha, Gabriela; Sancho, Ana Maria; Szerman, Natalia (Wiley, 2023)
Background: The increase in meat production would also imply an increase in the generation of by-products or edible offal. These by-products can be used, due to their high protein content, as a substrate to obtain hydrolysates with functional activities. This study aimed to valorize bovine lungs by producing hydrolysates with antioxidant capacity. Results: A response surface methodology study was carried out using a central composite design in which factors were temperature (43.2–76.8 C), enzyme/substrate ratio [ES: 0.65–4.85% (w/w)] using Alcalase 2.4 L/Flavourzyme (1:1) and pH (5.8–9.2). The antioxidant capacity of the obtained BLH (bovine lung hydrolysates) was evaluated by the ABTS, DPPH, and FRAP methods. The maximum antioxidant capacity was achieved at 53. C, ES ratio of 2.3% (w/w), and pH of 8.2. Under optimal hydrolysis conditions, the antioxidant capacity increased rapidly from the beginning of the reaction to 30 min, reaching a maximum at 120 min; then, it decreased until the end (180 min). The degree of hydrolysis increased as hydrolysis occurred up to a maximum of 45%. Molecular weight distribution of BLH evaluated by Tricine-SDS-PAGE and SEC-FPLC showed that bovine lung proteins hydrolyzed for 120 min presented low molecular weight peptides (<5 kDa), which are absent in the non-hydrolyzed sample. Conclusion: In this work, we optimized the variables for producing BLH with antioxidant capacity using commercial proteases in a short reaction time, making it a worthwhile strategy for the recovery of by-products from the meat industry. // Resumen: Antecedentes: El incremento en la producción de carne implicaría también un incremento en la generación de subproductos o despojos comestibles. Estos subproductos pueden ser aprovechados, por su alto contenido proteico, como sustrato para la obtención de hidrolizados con actividades funcionales. Este estudio tuvo como objetivo valorizar los pulmones bovinos mediante la producción de hidrolizados con antioxidantes capacidad. Resultados: Se realizó un estudio de metodología de superficie de respuesta utilizando un compuesto central diseño en el que los factores fueron temperatura (43,2-76,8 C), relación enzima/sustrato [ES: 0,65–4,85 % (p/p)] usando Alcalase 2,4 L/Flavourzyme (1:1) y pH (5,8–9,2). El antioxidante La capacidad de los BLH (hidrolizados de pulmón bovino) obtenidos fue evaluada por el Métodos ABTS, DPPH y FRAP. La máxima capacidad antioxidante se alcanzó en 53. Relación C, ES de 2,3% (p/p) y pH de 8,2. En condiciones óptimas de hidrólisis, la la capacidad antioxidante aumentó rápidamente desde el comienzo de la reacción hasta los 30 min, alcanzando un máximo a los 120 min; luego, disminuyó hasta el final (180 min). El grado de hidrólisis aumentó a medida que se producía la hidrólisis hasta un máximo del 45%. Molecular distribución de peso de BLH evaluada por Tricine-SDS-PAGE y SEC-FPLC mostró que proteínas de pulmón bovino hidrolizadas durante 120 min presentaron péptidos de bajo peso molecular (<5 kDa), que están ausentes en la muestra no hidrolizada. Conclusión: En este trabajo optimizamos las variables para producir BLH con antioxidante capacidad utilizando proteasas comerciales en un tiempo de reacción corto, lo que hace que valga la pena estrategia para la valorización de subproductos de la industria cárnica.